2013
DOI: 10.1002/jgrf.20130
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche grainflow on a simulated aeolian dune

Abstract: [1] Avalanches maintain the slipface of aeolian dunes, which alters their airflow characteristics and sediment dynamics, and results in the development of grainflow cross-bedding. We report on a series of experiments in which avalanches were observed on a 1:1 replica of a small (1.2 m brink height) transverse dune in the Dune Simulation Wind Tunnel under wind velocities of 8-11 m s -1 . Changes in slipface topography were observed photographically and measured utilizing a 3-D laser scanner with 1 mm 2 spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 38 publications
7
45
2
Order By: Relevance
“…Our data are broadly consistent with the results of Sutton et al [, ], who found that the frequency of grain flows generated in a laboratory dune depended on the sediment flux over the brinkline (formalized in our equation ). They also demonstrated that the relaxation angle controls the frequency of quasiperiodic cycles of storage and release of sediment from the upper slope in a manner that is also consistent with our equation .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data are broadly consistent with the results of Sutton et al [, ], who found that the frequency of grain flows generated in a laboratory dune depended on the sediment flux over the brinkline (formalized in our equation ). They also demonstrated that the relaxation angle controls the frequency of quasiperiodic cycles of storage and release of sediment from the upper slope in a manner that is also consistent with our equation .…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, under dry‐sand conditions the 30 m tall slip face had < θ c > = 32.2°–32.35° and the 17 m tall slip face had < θ c > = 32.2°–33°, with larger values (and hence larger differences) associated with slower winds. Combining these data with the < θ c > value of 34° from the 1.2 m tall slip face of the Sutton et al [, ], available data suggest that < θ c > varies inversely with slip‐face height, although this relationship must be valid only to some limit. The relaxation angle also has an inverse relationship with slip‐face height, reflecting an inverse relationship of the critical angle with height but no such relationship for the angle of repose. The 30 m tall slip face had a < θ c > − < θ r > value of ≈0.1°, the 17 m tall slip‐face had < θ c > − < θ r > values in the range of 0.2°–0.8°, and the 1.2 m tall slip face of Sutton et al [, ] had a < θ c > − < θ r > value of ≈2°.…”
Section: Discussionmentioning
confidence: 93%
“…Even subtle differences in barchan dune morphology may contribute to migration rate variations. For example, dunes possessing more concave slip faces may produce convergent avalanches advancing the lee slope faster than a comparable sized planar-shaped barchan (Sutton et al, 2013). A spectrum of slip face concavity can be observed across the study area; although it is unclear how much of a factor this was as moderate fluxes (~5m 3 m −1 yr −1 ) were observed for dunes with both concave and planar slip faces (e.g., Figs.…”
Section: Regional Aeolian Activitymentioning
confidence: 90%
“…The frequency of grain flows is thought to be dependent on factors such as the depositional rate (correlated to wind velocity) and sediment characteristics or environmental conditions which may affect grain movement or angle of repose (e.g. Allen, , ; Sweet & Kocurek,; McDonald & Anderson, , ; Nickling et al ., ; Cupp et al ., ; Breton et al ., ; Sutton, ; Sutton et al ., ,b; Pelletier et al ., ; Nield et al ., ). However, the mechanism of formation and initiation of grain flows is more complex.…”
Section: Introductionmentioning
confidence: 99%